2001
DOI: 10.1002/1097-0142(20010215)91:4<679::aid-cncr1051>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychosocial factors in the development of breast carcinoma: Part I

Abstract: The results of the current study found no evidence to support an independent association between these personality measures and the development of breast carcinoma. [See accompanying article on pages 686-97, this issue.]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
1
21
0
1
Order By: Relevance
“…Particularly, the type A behaviour item "sits on feelings-expresses feelings", which we also found not to be related to breast cancer risk, addressed the core of the cancer-prone personality. Numerous case-control studies 8,21,22 of variable methodologic quality have investigated the relationship between personality and risk of breast cancer with inconsistent results, a few studies 16 -18 reporting an increased risk also in relation to those characteristics (e.g., low type A behaviour) that were investigated in our study. However, some other studies have suggested that breast cancer patients' inhibition of emotional expression is a consequence rather than cause of the disease.…”
Section: Discordant Pair Analysesmentioning
confidence: 81%
“…Particularly, the type A behaviour item "sits on feelings-expresses feelings", which we also found not to be related to breast cancer risk, addressed the core of the cancer-prone personality. Numerous case-control studies 8,21,22 of variable methodologic quality have investigated the relationship between personality and risk of breast cancer with inconsistent results, a few studies 16 -18 reporting an increased risk also in relation to those characteristics (e.g., low type A behaviour) that were investigated in our study. However, some other studies have suggested that breast cancer patients' inhibition of emotional expression is a consequence rather than cause of the disease.…”
Section: Discordant Pair Analysesmentioning
confidence: 81%
“…Studies on stress and fibrocystic changes are limited. A Polish study found that women with fibrocystic changes had higher levels of anxiety, higher sensitivities to stress and increased stress responses 16) , whereas an Australian study observed no differences between normal women, benign breast diseases and breast carcinoma subjects, with respect to a number of psychosocial factors (such as life event stressors, social support, defense style, locus of control of behavior, emotional expression and control, self-esteem, anxiety, and depression) 17,18) . However, both studies were based on relatively small sample sizes and did not include measurements on stressful working conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Sieja investigated the psychological characteristics of women with fibrocystic breast changes and found that women with fibrocystic changes had higher levels of anxiety, higher sensitivities to stress and higher stress responses than healthy women 16) . However, the work of Price et al found no evidence to support an independent association between psychosocial factors and the development of breast carcinoma 17,18) . Although the processes by which exposure to psychosocial stress affects women's reproductive health are not yet fully established, several lines of evidence are available.…”
mentioning
confidence: 99%
“…1 In clinical and epidemiological studies, cancer progression, and to a lesser extent, cancer onset have been related to chronic stress, depression, lack of social support and other psychological factors. [2][3][4][5][6] Stress is a complex process encompassing environmental and psychosocial factors and initiates a cascade of information-processing pathways in both the central and peripheral nervous systems. Ultimately, the fight-or-flight stress responses in the autonomic nervous system (ANS) or the defeat/withdrawal responses in the hypothalamic-pituitary-adrenal axis (HPA) are generated and secrete catecholamines and cortisol, respectively (Fig.…”
Section: Introductionmentioning
confidence: 99%